The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/02626667.2020.1820012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of open access global climate services for hydrological data

Abstract: There is a high demand for openly accessible hydroclimatic data for climate change adaptation. Different data sources are available, however, discrepancy between the data can confuse users and should be evaluated and explained. This study, investigates how climate impact indicators (CIIs) developed for global users in the Copernicus Climate Change Service (C3S) are comparable to other openly available global data for water and climate. We found that, for temperature, datasets are comparable and climate impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…However, different number of GCMs used in different studies together with other assumptions, e.g., on reference period of bias-adjustment methods make the comparison of the impacts difficult. Merks et al (2020) found large differences between both current discharges and future changes projected with WW-HYPE using the full ensemble of 18 GCMs and those simulated with the variable infiltration capacity (VIC) model (Liang et al 1994;van Vliet et al 2015). The differences were partly attributed to propagation of change in areas with low annual precipitation and discharge, where it is difficult to predict runoff, and partly to differences between the models themselves (hydrological versus land-surface model), the evapotranspiration routines, and GCM ensembles.…”
Section: Present and Future Global Hydrological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, different number of GCMs used in different studies together with other assumptions, e.g., on reference period of bias-adjustment methods make the comparison of the impacts difficult. Merks et al (2020) found large differences between both current discharges and future changes projected with WW-HYPE using the full ensemble of 18 GCMs and those simulated with the variable infiltration capacity (VIC) model (Liang et al 1994;van Vliet et al 2015). The differences were partly attributed to propagation of change in areas with low annual precipitation and discharge, where it is difficult to predict runoff, and partly to differences between the models themselves (hydrological versus land-surface model), the evapotranspiration routines, and GCM ensembles.…”
Section: Present and Future Global Hydrological Conditionsmentioning
confidence: 99%
“…A variety of models can be strategically chosen to explore these key processes as well as a parameter space for the model calibration. Model performance also affects the agreement among the hydrological models (Merks et al 2020). A standardized evaluation, e.g., over smaller regions, would further help in these evaluations.…”
Section: Modeling a Change With A Large-scale Hydrological Modelmentioning
confidence: 99%
“…A quality assured production chain which is frequently used in climatic services (including hydro services; [17]) was implemented to produce Climate Indicators (CI) and Water Indicators (WI) from Essential Climate Variables (ECV) available in the Climate Information platform (Figure 1). The production follows a rigorous quality assurance protocol developed in previous projects and adjusted to fit the current needs.…”
Section: Data Productionmentioning
confidence: 99%
“…The ensemble of CMIP5 models previously used in a Copernicus Climate Change Service Sectoral Information System (C3S SIS, [17]) was also used to provide a complete global coverage. The ensemble was modified to fit the current requests (different reference period (1981-2010), which differs from C3S (1971-2000)); the ensemble is also available in Appendix A.…”
Section: Global and Regional Climate Modelsmentioning
confidence: 99%
See 1 more Smart Citation